Gender differences involved in the pathophysiology of the perinatal hypoxic-ischemic damage - Murden, S; Borbélyová, V; Laštůvka, Z; Mysliveček, J; Otáhal, J; Riljak, V (Physiological research, 2019)
Hypoxic-ischemic encephalopathy (HIE) is a neonatal condition that occurs as a consequence of perinatal asphyxia, which is caused by a number of factors, commonly via compression of the umbilical cord, placental abruption, severe meconium aspiration, congenital cardiac or pulmonary anomalies and birth trauma. Experimental studies have confirmed that male rat pups show a higher resistance to HIE treatment. Moreover, the long-term consequences of hypoxia in male are more severe in comparison to female rat pups. These sex differences can be attributed to the pathophysiology of hypoxia-ischemia, whereby studies are beginning to establish such gender-specific distinctions. The current and sole treatment for HIE is hypothermia, in which a reduction in temperature prevents long-term effects, such as cerebral palsy or seizures. However, in most cases hypothermia is not a sufficient treatment as indicated by a high mortality rate. In the present review, we discuss the gender differences within the pathophysiology of hypoxia-ischemia and delve into the role of gender in the incidence, progression and severity of the disease. Furthermore, this may result in the development of potential novel treatment approaches for targeting and preventing the long-term consequences of HIE.
Keywords: oxidační stres; Male; Hypoxia-Ischemia, Brain; Sex Characteristics; Brain; mužské pohlaví; asfyxie novorozenců; pohlavní dimorfismus; mozková hypoxie a ischemie; novorozenec; Animals; lidé; ženské pohlaví; Humans; zvířata; Infant, Newborn; mozek; apoptóza; Female; Oxidative Stress; Asphyxia Neonatorum; Apoptosis